PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN RESIKO BISNIS TERHADAP KEBIJAKAN HUTANG - Refdatul Husna; - Wahyudi (Trunojoyo University of Madura, 2016)
The purpose of this study was to examine the influence of Firm Size, Profitability and Business Risk on Debt Policy of companies manufacturing industry consumption listed in Indonesian Stock Exchange for the period from 2012 to 2014. The population in this study amounted to 37 companies which are all companies manufacturing industry consumption listed in Indonesian Stock Exchange during the period 2012 to 2014. The sample used in this study is a companies that meets the criteria as set out in this study to obtain 28 companies. The data obtained derived from the annual report and financial report of the banks published. The analysis technique used in this research is multiple linear regression to test the classical assumption first. The result showed that the Firm Size is not significantly effects on Debt Policy. While Profitability and Business Risk have a significant influence on Debt Policy. The ability of independent variables (Firm Size, Profitabilty and Business Risk) in explaining the dependent variable (Debt Policy) is 13,9%. The remaining 86,1% is explained by variable such as Non-debt Tax Shield, Tangilibity, Institusional Ownership, Free Cash Flow, Asse Structure, Managerial Ownership and Dividend Policy.